Timing and Temporality in Islamic Philosophy and Phenomenology of Life - Tymieniecka, Anna-Teresa.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
From time immemorial, concern with timing of life has been crucial for the regulation of human praxis as well as for the philosophical quest to understand existence by seeking its meaning. The two used to inform each other, until modernity, when they parted. In spite of the extensive progress in manipulating change and motion, and of the abundance of metaphysical attempts to enlighten human beings about their fate, the puzzling nature of temporality and timing of reality remains controversial. The present collection of studies seeks a new answer by initiating a novel investigation informed by the ancient wisdom of the Greaco-Arabic-Islamic sources and inheritance, on the one side, and the contemporary discernment of Occidental phenomenology of life, on the other, in a common dialogical effort to unravel this great enigma of existence. Papers by: Anna-Teresa Tymieniecka, William C. Chittick, Reza Akbarian, Daniela Verducci, Michael F. Andrews, Seyyed Mohammed Khamenei, Nader El-Bizri, Mehdi Aminrazavi, Massimo Durante, Abdul Rahim Afaki, Maria-Chiara Teloni, A.L. Samian, Kathleen Haney, Jad Hatem, Robert J. Dobie, Michel Dion.
Section I -- The View from Nowhere: Ibn al-'Arab? on the Soul's Temporal Unfolding -- The Great Metamorphosis of The Logos of Life in Ontopoietic Timing -- Temporal Origination of the Material world and Mulla Sadra's Trans-substantial Motion -- The Timing of The Ontopoiesis of Life -- Section II -- Edmund Husserl: The Genesis and Origin of Time -- Time, Temporal, and Temporality -- Some Phenomenological and Classical Corollaries on Time -- Section III -- M?r D?m?d on Time and Temporality -- Historical and Messianic Time: The Structure of Subjectivity and the Question of Judgement -- The Historicality of Linguistic Signs and the Ahistoricality of Meanings: The Role of Divine Neologisms in the Making of Islamic-Arab Tradition -- Section IV -- Time and The Formation of the Human Person: a Comparison of Edith Stein's and Martin Heidegger's Thoughts -- Virtues in Al-Biruni's Philosophy of Science -- The Ontopoietic Timing of Life Versus The Kairic Unfolding of The Trans-Natural Destiny (A-T. Tymieniecka) -- Pure Love in Mulla Sadra -- Section V -- The Phenomenology of Wujud In the Thought of Ibn Al-'Arabi -- "Ibn Khaldûn's Concept of History and the Qur'anic Notions of Economic Justice and Temporality".
Keywords: PHILOSOPHY (GENERAL).; PHILOSOPHY, MEDIEVAL; METAPHYSICS; PHILOSOPHY, MODERN; PHENOMENOLOGY; PHILOSOPHY; PHENOMENOLOGY; NON-WESTERN PHILOSOPHY; MEDIEVAL PHILOSOPHY; METAPHYSICS; HISTORY OF PHILOSOPHY